Antusias Belajar Mahasiswa dengan Model Pembelajaran Small Group Discussion di Departemen Sosiologi FISIP Unhas - Feby Awaliah; Hasmawati, Hasmawati; Putu Wijangga; Muh. Fathan Halim; Nurkhalisa Kurnia Umar (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to provide an overview of how the implementation of small group discussions in the Department of Sociology FISIP Hasanuddin University and provide an overview of how the implementation of small group discussions carried out by students both internally and between groups. In addition, this study also aims to describe the factors that influence student learning enthusiasm in the small group discussion learning model. This research was conducted from 28 May to 14 June 2023 at the Department of Sociology, Faculty of Social and Political Sciences, Hasanuddin University. There were 63 students as respondents in this study, where the number was determined using random sampling technique. The research method used as a problem-solving instrument in this research is using a descriptive quantitative approach, using a research instrument, namely a questionnaire and direct interviews with respondents. The results of this study indicate that small group discussions have been quite good in their implementation at the Department of Sociology FISIP Unhas and small group discussions have also been quite effective because most of the respondents' answers show a positive response, namely being quite involved in the preparation and implementation of the application of small group discussions, although in their implementation there are still many respondents who pay less attention to preparation or planning before the group material is presented. The factors that influence student learning enthusiasm are the opportunity for all students to be directly involved in the learning process, the process of solving problems together, and the freedom to express opinions.